A Lecture on the Performance of Beauty. Issue 1 (1st April 2014) - Hay, Deborah
What if the question, 'what if every cell in my body at once has the potential to simultaneously perceive beauty and surrender beauty each and every moment as time passes?' is about the question, without seeking an answer?